Modification of Biocorrosion and Cellular Response of Magnesium Alloy WE43 by Multiaxial Deformation - Natalia Anisimova; Natalia Martynenko; Keryam Novruzov; Olga Rybalchenko; Mikhail Kiselevskiy; Georgy Rybalchenko; Boris Straumal; Gennady Salishchev; Almagul Mansharipova; Aigul Kabiyeva; Maratbek Gabdullin; Sergey Dobatkin; et al. (Metals, 2022)
The study shows that multiaxial deformation (MAD) treatment leads to grain refinement in magnesium alloy WE43. Compared to the initial state, the MAD-processed alloy exhibited smoother biocorrosion dynamics in a fetal bovine serum and in a complete cell growth medium. Examination by microCT demonstrated retardation of the decline in the alloy volume and the Hounsfield unit values. An attendant reduction in the rate of accumulation of the biodegradation products in the immersion medium, a less pronounced alkalization, and inhibited sedimentation of biodegradation products on the surface of the alloy were observed after MAD. These effects were accompanied with an increase in the osteogenic mesenchymal stromal cell viability on the alloy surface and in a medium containing their extracts. It is expected that the more orderly dynamics of biodegradation of the WE43 alloy after MAD and the stimulation of cell colonization will effectively promote stable osteosynthesis, making repeat implant extraction surgeries unnecessary.